Poland and the European Union - Cordell, Karl, 1956- (Europe and the nation state., 2000)
This authoritative volume assesses how the recently democratised political system in Poland is adapting to the challenges posed by the country's desire to "rejoin Europe". Its excellent panel of highly respected Polish academics considers various issues not generally well-known to the English-speaking world, but of great importance in the light of Poland's impending entry into the European Union